Pronounced changes in paleo-wind direction and dust sources during MIS3b recorded in the Tacheng loess, northwest China. (30th June 2020) - Cheng, Liangqing; Song, Yougui; Sun, Huanyu; Bradák, Balázs; Orozbaev, Rustam; Zong, Xiulan; Liu, Huifang
Abstract: Central Asia loess deposits can yield detailed records of aridification across the Asian interior, as well as the atmospheric circulation. In this study, we presented grain size, heavy mineral assemblage, rock magnetism and anisotropy of magnetic susceptibility of a loess section in the Tacheng Basin in Xinjiang region, NW China. The results of anisotropy of magnetic susceptibility indicated that a near-surface SE wind prevailed in the Tacheng area since Marine Isotope Stage (MIS) 3, while a near-surface SW prevailing wind developed during MIS3b. We inferred that the change of wind direction was due to glacial advance during MIS3b. Combining the result of anisotropy of magnetic susceptibility with grain size, heavy mineral assemblage data and previously published low-field mass susceptibility revealed that dust transported by the near-surface SW wind had a greater ability to enhance magnetic susceptibility and higher amphibole/epidote ratio. Additionally, a strong Siberian High during Heinrich Event (H)5 at ca. 48 ka blocked the advection of moisture into the region via mid-latitude westerlies, causing glacial recession and the weakening of the prevailing SW wind. Our study has implications for identifying changes in paleo-wind direction and dust source, which can aid understanding of the influence of westerlies and the Siberian High on dust accumulation, as well as their interactions.